Risk factors for the delayed discharge from anesthesia intensive care unit: a single-center retrospective study - Yue Qian; Jing Hao; Wei Zhu; Yan Yang; Zhuan-yun Zhang; Lu-yang Zhou; Xiao-ping Gu; Zheng-liang Ma; Yu-e Sun (BMC Anesthesiology, 2025)
Abstract Background A single-center retrospective study was designed to investigate the risk factors associated with delayed discharge from the Anesthesia Intensive Care Unit (AICU). Methods This retrospective study involved patients admitted in the AICU from January 2017 to December 2022. Risk factors for the delayed discharge from the AICU were analyzed by the binary multivariate logistic regression analysis. Nomogram was constructed to predict the risk of delayed discharge from AICU. The performance of the nomogram was assessed using the receiver operating characteristic curve and calibration curve. A decision curve analysis was also performed to determine the net benefit threshold of prediction. Results A total of 14,338 patients admitted in the AICU were retrospectively recruited, involving 9,271 males and 5,067 females. The incidence of delayed discharge from the AICU in the cohort was 1.54% (221/14,338). Binary multivariate logistic regression analysis showed that younger than 18 years or older than 64 years, the American Society of Anesthesiologists physical status of class III-IV, body mass index of less than 18 kg/m2 or greater than 25 kg/m2, preoperative complications, emergency surgeries and intraoperative massive hemorrhage were risk factors for the delayed discharge from an AICU. We utilized nomograms to visually express data analysis results. Based on receiver operating characteristic analysis, calibration plots, and decision curve analysis, we concluded that the nomogram model exhibited excellent performance. Patients undergoing spine surgeries suffered from the highest proportion of delayed discharge from the AICU, followed by those receiving orthopedic and vascular surgeries. Postoperative hemorrhage was the major cause of delayed discharge from an AICU, followed by septic shock, hypoperfusion and pulmonary insufficiency. Conclusion The incidence of delayed discharge from the AICU in a single-center tertiary hospital is 1.54%. It is influenced by various risk factors, including age, ASA physical status classification, BMI, preoperative complications, type of surgery and intraoperative blood loss. The nomogram model exhibits excellent performance. Trial registration The single-center retrospective study was approved by the Ethics Committee of Nanjing Drum Tower Hospital (No. 2021-563-01, Data: 22 November 2021) and registered on the Chinese Clinical Trial Registry (No. ChiCTR2300078251, Data: 01 December 2023).